TRANSFORMASI KEILMUAN PESANTREN TAHFIDZ DAARUL QUR’AN CIKARANG DAN IMPLIKASI BIMBINGAN KONSELING - Nurina, Putri (Institut Daarul Qur'an Jakarta, Indonesia, 2021)
Pesantren is an old educational institution and is widespread in the territory of Indonesia. This can be proven by the existence of educational activities in the form of Islamic boarding schools in the early 16th century on the slopes of Mount Karang, Banten and these activities were open to the public. ntil now, the number of Islamic boarding schools in all regions of Indonesia is increasing. Initially, education in the pesantren was only in the form of lessons derived from religious books which are often referred to as the yellow book. However, currently, the pesantren education system has experienced many developments, namely not only studying and deepening the yellow book, but general knowledge, technology, and skills. The development of pesantren continues with the existence of pesantren that combines general education with the obligation of its students to memorize the Al-Qur'an which is known as the Tahfidz Islamic Boarding School. In addition, pesantren also need counseling for their students. In contrast to formal schools which prioritize aspects related to education, pesantren prioritize religious matters. Therefore, a religious counseling in the pesantren is needed to assist and accompany the students in their development tasks.